Disease characteristics in patients with juvenile- and adult-onset systemic lupus erythematosus: A multi-center comparative study - Sherif M Gamal,; Nermeen Fouad,; Nora Yosry,; Wael Badr,; Nesreen Sobhy, (Archives of Rheumatology, 2022)
Objectives: This study aims to compare disease characteristics in patients with juvenile-onset systemic lupus erythematosus (JSLE) and adult-onset systemic lupus erythematosus (ASLE). Patients and methods: Between June 2010 and March 2020, a total of 186 patients with JSLE (23 males, 163 females; median age: 25 years; range, 20 to 30.3 years) and 236 patients with ASLE (23 males, 213 females; median age: 35 years; range, 29 to 40 years) were retrospectively analyzed. Clinical and laboratory data, treatment received, Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) and Systemic Lupus International Collaborating Clinics (SLICC)/ACR Damage Index (SDI) scores, comorbidities and deaths were compared between the groups. Results: The JSLE patients showed statistically significant higher constitutional manifestations, cardiac manifestations, serositis, nephritis, end-stage renal disease, neurological manifestations, gastrointestinal manifestations, secondary vasculitis, Raynaud’s, livedo-reticularis, dry mouth, dry eye, ocular manifestations, avascular necrosis, hematological manifestations, and hypocomplementemia (p<0.001, p=0.016, p=0.005, p=0.001, p=0.04, p<0.001, p<0.001, p<0.001, p=0.002, p=0.043, p=0.004, p=0.03, p<0.001, p=0.01, p<0.001, and p=0.001, respectively). Median SLEDAI scores were statistically significant higher in the JSLE group, both at onset (p<0.001) and in the final follow-up visit (p<0.001). Median SLICC scores were also higher in the JSLE group (p<0.001). Mycophenolate mofetil and intravenous pulse steroids were more frequently used in the juvenile group (p<0.001 and p=0.03, respectively). Hypertension, dyslipidemia, and avascular necrosis were found to be statistically significantly higher in the JSLE group (p<0.001, p=0.006, and p=0.01, respectively). The mortality rate was statistically significantly higher in the JSLE group than the ASLE group (p<0.001). Conclusion: The JSLE patients showed more serious manifestations, higher disease activity, higher damage index, and mortality rate compared to ASLE patients. These results suggest the need of a regular follow-up and close surveillance of JSLE patients.